2017
DOI: 10.1136/bmjopen-2017-016800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Community ART Groups on retention-in-care among patients on ART in Tete Province, Mozambique: a cohort study

Abstract: ObjectivesEstimate the effect of participation in Community ART Groups (CAG) versus individual care on retention-in-care (RIC) on antiretroviral therapy (ART).DesignRetrospective cohort study.SettingHigh levels of attrition (death or loss-to-follow-up (LTFU) combined) on ART indicate that delivery models need to adapt in sub-Saharan Africa. In 2008, patients more than 6 months on ART began forming CAG, and took turns to collect ART refills at the health facility, in Tete Province, Mozambique,.Participants2406 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 29 publications
6
64
1
3
Order By: Relevance
“…Both clients and HCWs consistently self-reported that CARGs improved adherence and reduced client loss to followup. This is consistent with quantitative evaluations of pilot programmes, which found that clients in CAGs had lower rates of loss to follow-up [11,[22][23][24]. Once sufficient person-time in CARGs has accrued, quantitative analyses should be done to evaluate the impact of CARG membership on retention and viral suppression.…”
Section: Discussionsupporting
confidence: 70%
“…Both clients and HCWs consistently self-reported that CARGs improved adherence and reduced client loss to followup. This is consistent with quantitative evaluations of pilot programmes, which found that clients in CAGs had lower rates of loss to follow-up [11,[22][23][24]. Once sufficient person-time in CARGs has accrued, quantitative analyses should be done to evaluate the impact of CARG membership on retention and viral suppression.…”
Section: Discussionsupporting
confidence: 70%
“…The practical benefits of sharing the logistical constraints for ART collection and facilitating patients retention in care is mirrored in a quantitative analysis of this model in Malawi [10] and Mozambique [14], and was also observed in a study of a similar model of ART refill distribution, conducted in South Africa [15]. …”
Section: Discussionmentioning
confidence: 93%
“…Differentiated models of ART delivery can be broadly classified into individual models (facility or out‐of‐facility) and group models (health worker or client‐managed) . Several group and out‐of‐facility individual models have demonstrated promising results, including health worker‐led ART refill groups in South Africa , patient‐led community ART groups in Mozambique and community ART distributions points in the Democratic Republic of Congo . However, health worker‐managed or patient‐managed group strategies may require additional resources in order to scale‐up implementation, and concerns have been raised about their sustainability .…”
Section: Introductionmentioning
confidence: 99%